2019
DOI: 10.1080/22221751.2019.1663130
|View full text |Cite
|
Sign up to set email alerts
|

Occult HBV infection in Chinese blood donors: role of N-glycosylation mutations and amino acid substitutions in S protein transmembrane domains

Abstract: Occult hepatitis B virus infection (OBI) is a low-level asymptomatic phase of HBV infection. Evidence of OBI clinical relevance is emerging but the mechanisms of its occurrence remain unclear. In this study, the molecular characteristics of 97 confirmed OBI from Chinese blood donors were analyzed and relevant mutations were identified. Recombinant HBsAg bearing these mutations were expressed in vitro and the antigenicity and HBsAg secretion properties were analyzed. Results showed that 45 (46.4%) genotype B, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Studies have shown that some patients with OBI harbour a higher proportion of mutations in the preS/S region than patients with CHB, which may result in a reduced antigenicity for HBsAg detection or impairment in HBsAg production or secretion. 7,12,[36][37][38][39][40][41] The mutations in pre-S1 may also alter the B and T epitopes that affect immune recognition. 7 However, HBV DNA isolated from individuals with OBI is fully replication competent in vitro, 42 and the virus can also be transmitted via blood transfusion or organ transplantation.…”
Section: Virology Epigenetics and Immunology Of Obimentioning
confidence: 99%
“…Studies have shown that some patients with OBI harbour a higher proportion of mutations in the preS/S region than patients with CHB, which may result in a reduced antigenicity for HBsAg detection or impairment in HBsAg production or secretion. 7,12,[36][37][38][39][40][41] The mutations in pre-S1 may also alter the B and T epitopes that affect immune recognition. 7 However, HBV DNA isolated from individuals with OBI is fully replication competent in vitro, 42 and the virus can also be transmitted via blood transfusion or organ transplantation.…”
Section: Virology Epigenetics and Immunology Of Obimentioning
confidence: 99%
“…Since misfolded proteins are usually retained within cells by the ER protein quality control [ 15 ], the altered antigenicity of hyper-glycosylated HBsAg may be attributed to epitope shielding rather than to mutation-induced conformational changes. With this in mind, it is not surprising that N-glycosylation mutations are increasingly reported in individuals with occult HBV infection (OBI), characterized by sustained viral replication in the absence of detectable HBsAg [ 59 , 61 , 64 ] ( Table 1 ). This observation has great clinical relevance, highlighting the importance of complementary assays for accurate diagnosis of HBV infection in HBsAg-negative patients.…”
Section: Hbv N-glycosylation and The Interaction With The Host Immmentioning
confidence: 99%
“…More specifically, blood with HBsAg ELISA R-NR and NAT NR results may place recipients at risk of HBV transmission, due to the extremely low levels of HBsAg and HBV DNA, respectively. Previous studies have shown that mutations in the S region and basic core promoter (BCP) and pre-core (PC) of HBV can affect the detection of HBsAg and viral nucleic acid [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%